Profil Miskonsepsi Siswa pada Materi Bentuk Aljabar di Sekolah Menengah Pertama Negeri Kota Banda Aceh - Aulia, Dinda; Zubainur, Cut Morina; Khairunnisak, Cut (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
Learning loss has an impact on various problems, including misconceptions by students when recognizing and learning algebraic operations. This research aims to identify the profile of students' misconceptions in algebraic concepts as a consequence of learning loss due to the Covid-19 pandemic in public junior high school in Banda Aceh. The study adopts a quantitative approach. The population of the research consists of all eighth-grade students in public junior high school in Banda Aceh and the sample comprises 27 students from one of these schools. The sample was obtained through purposive sampling, selecting students from the top-ranked junior high school in Banda Aceh, known for having the highest average scores. Misconceptions were assessed using an online-based cognitive diagnostic test on algebraic concepts. Data analysis was conducted by examining the composition of misconceptions based on their types. The research findings indicate that the majority of students experience misconceptions, with 25.20% experiencing misconceptions in notation, 20.37% in generalization, 8.98% in understanding symbols, 9.97% in applying rules, 1.14% in notation and generalization, 0.57% in notation and understanding symbols, and 2% in generalization and applying rules. This study indicates a necessity to an analysis of the causes of misconceptions and efforts to minimize students' misconceptions in algebraic concepts, such as implementing cognitive conflict learning or remedial teaching.